2009
DOI: 10.1016/j.jcrs.2008.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront aberrations in eyes with decentered ablations

Abstract: Eyes with decentered ablations had a significantly higher magnitude of induced aberrations and lower UCVA than eyes with well-centered ablations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 24 publications
2
21
0
3
Order By: Relevance
“…These results indicated that the centration errors exerted a significant influence on the residual wavefront aberrations [8]. Decentrations during refractive surgery may account for a portion of the postoperative increases in higherorder aberrations [9,10].…”
Section: Introductionmentioning
confidence: 78%
“…These results indicated that the centration errors exerted a significant influence on the residual wavefront aberrations [8]. Decentrations during refractive surgery may account for a portion of the postoperative increases in higherorder aberrations [9,10].…”
Section: Introductionmentioning
confidence: 78%
“…These results revealed that the decentration had an important influence on the postoperative wavefront aberrations [8]. Wang et al reported that mean pupil centroid shift was 0.29 mm during wavefront-guided corneal ablation [9].…”
Section: Introductionmentioning
confidence: 92%
“…One such study was a retrospective chart review of 3719 eyes undergoing LASIK for myopia, which found a total of 46 eyes (1.2%) with topographically-determined decentration. 44 Decentration of the ablation profile can be caused by a number of intraoperative factors, including treatment displacement (a shift in the specified treatment location), eye movements such as drift, or poor patient fixation. 45 Stromal drying has also been suggested to contribute to decentration risks, as this may induce poor patient visualization of the fixation beam.…”
Section: Higher Order Aberrationsmentioning
confidence: 99%
“…To support suspicion of clinical relevance, they also correlated ablation profile decentration with a lower uncorrected visual acuity. 44 …”
Section: Higher Order Aberrationsmentioning
confidence: 99%